2010
DOI: 10.1186/1471-2180-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate enhances expression of the endocarditis and biofilm associated pilus locus, ebpR-ebpABC, in Enterococcus faecalis

Abstract: BackgroundWe previously identified ebpR, encoding a potential member of the AtxA/Mga transcriptional regulator family, and showed that it is important for transcriptional activation of the Enterococcus faecalis endocarditis and biofilm associated pilus operon, ebpABC. Although ebpR is not absolutely essential for ebpABC expression (100-fold reduction), its deletion led to phenotypes similar to those of an ebpABC mutant such as absence of pili at the cell surface and, consequently, reduced biofilm formation. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 33 publications
1
42
0
1
Order By: Relevance
“…Their genetic organization is highly conserved in each species, but the E. casseliflavus isolates lack an ebpB homolog. Similar to E. faecalis, E. faecium and E. gallinarum also have ebpR (encoding a positive regulator of the ebp operon in E. faecalis [5,6]) in the same position (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Their genetic organization is highly conserved in each species, but the E. casseliflavus isolates lack an ebpB homolog. Similar to E. faecalis, E. faecium and E. gallinarum also have ebpR (encoding a positive regulator of the ebp operon in E. faecalis [5,6]) in the same position (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…pTEX5585 is a pTCV-lac-derived vector containing the ebpA promoter, the 5Ј-UTR, and the first 41 nucleotides (nt) of the coding region upstream of a LacZ coding region (6). As shown in Fig.…”
Section: Figmentioning
confidence: 99%
“…It has been demonstrated that deletion of ebpR leads to reduced levels of the ebpABC mRNA, as evaluated by quantitative real-time PCR (qRT-PCR), and of pili, as evaluated by Western blotting (5). Many environmental factors affect pilus production, including culture medium (tryptic soy broth [TSB] versus brain heart infusion [BHI]), serum, and bicarbonate (6). In a recent study, Bourgogne et al demonstrated that the addition of bicarbonate to culture media enhanced the expression of the ebpR and ebpABC locus (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations